FENOMENA PERNIKAHAN KECELAKAAN DALAM KEHIDUPAN REMAJA DI DESA TERARA LOMBOK TIMUR - Mia Dwi Putri (Universitas Hamzanwadi, 2022)
Accidental marriage is marriage because it is already pregnant where this pregnancy was not planned by the couple. In this day and age, there are many cases of accidental marriages, especially with the uncontrolled life of teenagers so that it provides space for teenagers to do this. What is discussed in this study is to determine the embryo of the emergence of accidental marriages, the dynamics of the existence of accidental marriages and the impact of accidental marriages on adolescents.This research is a descriptive research with a qualitative approach. Data collection techniques through observation, interviews and documentation. The data and data sources in this study are primary data and secondary data. While the data analysis technique used is qualitative data analysis through data collection, data reduction, data presentation and drawing conclusions. Based on the results of this study, it can be concluded that (1) the embryo of the emergence of accidental marriages in the lives of adolescents in Terara village is due to lack of religious education, parents provide freedom, peer influence, internet influence, no customary sanctions, broken home family influences, and lack of sex education. (2) the dynamics of the existence of accidental marriages in adolescent life are grouped into 3 typologies of adolescent characters, namely early adolescence, middle adolescence and late adolescence. (3) The impact of accidental marriages experienced by adolescents are psychological impacts and social impacts.